1997
DOI: 10.1046/j.1464-410x.1997.00251.x
|View full text |Cite
|
Sign up to set email alerts
|

Lack of correlation between blood fibrinolysis and the immediate or post‐operative blood loss in transurethral resection of the prostate

Abstract: Objective To evaluate whether the activation of the increase in systemic t-PA activity and t-PA antigen, coinciding with a significant drop in PAI activity. Postextrinsic tissue-type plasminogen activator-related fibrinolysis is implicated in the blood loss in patients operatively, PAI activity and PAI-1 antigen increased. The formation of plasmin was indicated by a fall in with benign prostatic hyperplasia, undergoing transurethral prostatic resection (TURP).the plasma concentration of Plg activity and Plgant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

1999
1999
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 3 publications
0
18
0
1
Order By: Relevance
“…Urine and urothelium contain high concentrations of plasminogen activators that facilitate the lysis of clots [4]. Therefore, administration of antifibrinolytic agents might be beneficial in reducing the amount of postoperative blood loss resulting from TURP.…”
Section: Introductionmentioning
confidence: 99%
“…Urine and urothelium contain high concentrations of plasminogen activators that facilitate the lysis of clots [4]. Therefore, administration of antifibrinolytic agents might be beneficial in reducing the amount of postoperative blood loss resulting from TURP.…”
Section: Introductionmentioning
confidence: 99%
“…The haemoglobin concentration decreased throughout the study period, as did the haematocrit ( Table 1). The results were evaluated both with (+) and without (−) correction for haemodilution, the method of correction having been described earlier [ 8].…”
Section: Resultsmentioning
confidence: 99%
“…At the end of TURP all patients were given loop diuretics (bumetanid 1 mg) intravenously, and a 22 F two‐way catheter inserted and retained in situ until the urine was clear. The removed tissue was weighed and the blood loss calculated as described previously [ 8].…”
Section: Methodsmentioning
confidence: 99%
“…Bell et al [19] reported that the thromboelastogrphy (TEG) parameters reflect a hypercoagulable state during and after TURP and that this change is caused by the inhibition of the fibrinolytic system. Conversely, Nielsen et al [20] concluded that the fibrinolytic system is activated during TURP due to surgical trauma. Although these 2 studies demonstrated conflicting results regarding the change of the fibrinolytic system, both of these reports failed to provide information about the amount of irrigating fluid used and absorbed.…”
Section: Discussionmentioning
confidence: 99%